Creative and Responsive Advocacy for Reconciliation: The Application of Gladue Principles in Administrative Law - Martin, Andrew (McGill Law Journal / Revue de droit de McGill, 2020)
As a response to the estrangement and alienation of Indigenous peoples from the Canadian justice system, Gladue principles are central to reconciliation in sentencing and other criminal law contexts. However, the role of Gladue principles in administrative law more broadly remains uncertain. In this paper, I argue that the factors underlying Indigenous peoples’ estrangement and alienation from the justice system indicate estrangement and alienation from the administrative state itself, and thus Gladue principles appropriately apply in administrative law contexts. Using the results of a comprehensive search of reported decisions by tribunals and by courts on judicial review, I analyze the reasons given by administrative decision-makers and judges for applying or declining to apply Gladue principles. I argue based on this analysis that Gladue principles will most clearly apply in decisions about a penalty or a benefit for an Indigenous person, and can also apply—albeit in a way that requires more creativity—where the decision is about neither a penalty nor a benefit. On this basis, I provide recommendations for counsel, administrative decision-makers, judges, legislators, and executive authorities to better realize the potential of Gladue principles.